If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + 8) + (n + -12) = 0 Reorder the terms: (8 + n) + (n + -12) = 0 Remove parenthesis around (8 + n) 8 + n + (n + -12) = 0 Reorder the terms: 8 + n + (-12 + n) = 0 Remove parenthesis around (-12 + n) 8 + n + -12 + n = 0 Reorder the terms: 8 + -12 + n + n = 0 Combine like terms: 8 + -12 = -4 -4 + n + n = 0 Combine like terms: n + n = 2n -4 + 2n = 0 Solving -4 + 2n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2n = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 2n = 0 + 4 2n = 0 + 4 Combine like terms: 0 + 4 = 4 2n = 4 Divide each side by '2'. n = 2 Simplifying n = 2
| 5x^3-19x^2+4x=32 | | 2+7x=4x+-2 | | 5(t-3)-2=-30 | | 14-z=2 | | 1+12(x-5)= | | 2m+-1nx=x+4 | | 5x^3+45=2x^2+18 | | 7x-6-3x=6x-5 | | 12+2b=60 | | -2p+8=5p-10 | | 60+50.4x=57.95x | | 3n+3=61 | | 8x+9=5x-29 | | 12(d+2)=3(d-8)+9d | | w-2w=4w+20 | | -13=-5a-(-12) | | 6x-3=-87 | | 5x+8=3y-6 | | 6.42-10*.392=2.5 | | 90+5x-9+3x+35=180 | | 9=T+6 | | -6x-5=10 | | 6-3x=5x-10+16 | | q-8=-14 | | ln(x^2-25)=0 | | 2y=78-5x | | Log(10)(x+3)-log(10)(x-3)=1 | | 10x+4x-3x=5-6x | | (x*2)-7=19 | | C=-4c | | 3(k-15)=-18 | | 5x=78-2y |